Novel Drugs Targeting the Epidermal Growth Factor Receptor and Its Downstream Pathways in the Treatment of Colorectal Cancer: A Systematic Review. (14th October 2012) - Merla, Amartej; Goel, Sanjay
Abstract : Colorectal cancer is the second most common malignancy among men and women in the United States, and the 5-year survival rate remains poor despite recent advances in chemotherapy and targeted agents. The mainstay of therapy for advanced disease remains the cytotoxic chemotherapy including 5-FU, irinotecan, and oxaliplatin. The USFDA approval and introduction of targeted therapies, including cetuximab and panitumumab (monoclonal antibodies targeting the epidermal growth factor receptor (EGFR)) and bevacizumab (monoclonal antibody targeting the vascular epithelial growth factor (VEGF)), has improved the median survival of patients with metastatic colorectal cancer to around 24 months. Clearly, better and more efficacious drugs are needed, and target-specific agents remain the future of cancer treatment. On this front, rapid advances are being made, which are likely to change the future of the management of metastatic colorectal cancer. However, absence of specific biomarkers for the use of targeted agents, in the subset of population who will benefit from the treatment, remains a major drawback. In this paper, we review agents that are in phases 1 and 2 clinical development, specifically targeting the EGFR and its subsequent downstream pathways.